PERANCANGAN APLIKASI PEMESANAN TIKET BUS ONLINE PADA PT REHOBOT BETHANIA TRANS - Tony Darmanto; Kartono Kartono; Welly Wiranatha (LPPM Universitas Widya Dharma Pontianak, 2023)
PT Rehobot Bethania Trans Pontianak is a company engaged in public transportation. With the ticket purchasing system still manually and not yet computerized, the company sometimes forgets to record the ticket buyer's name, this makes the company experience difficulties in recording data for each prospective passenger. In this study the authors used qualitative analysis methods. The method of qualitative analysis is to collect data both through observation and interviews which are then used as a description of the application design. As for the application design, the author uses the PHP programming language and MySQL database. At the system design stage the author uses the Unified Modeling Language (UML), where this UML is a standard modeling language consisting of a series of integrated diagrams, while for application modeling the author uses several diagrams, namely use case diagrams, activity diagrams, Sekuensial diagrams and class diagrams. Meanwhile, the research method used during the research is the waterfall method, namely the creation of a structured and sequential website starting from system analysis, application design, coding to the testing phase and normalization. Thus customers do not experience difficulties when they want to order tickets online. The conclusion obtained by the author is that this application can display logins, registers, ticket reservations, ticket payments, view departure schedules, order statuses and payment confirmations. Keywords: Application, Booking, Online, Waterfall